PENERAPAN MODEL PEMBELAJARAN PENCAPAIAN KONSEP DALAM MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR - Aini Husna (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the implementation of the Concept Attainment learning model in improving elementary school students’ understanding of science concepts. The Concept Attainment model, developed by Jerome S. Bruner, emphasizes inductive thinking processes through the presentation of examples and non-examples so that students can independently discover a concept. This research employed a quantitative approach using a quasi-experimental method involving fifth-grade elementary school students as research subjects. Data were collected through concept understanding tests administered before and after the treatment, as well as classroom observations. The results indicate that the implementation of the Concept Attainment model significantly improves students’ understanding of science concepts compared to conventional teaching methods. Students became more active in identifying concept characteristics, classifying information, and drawing conclusions independently. Therefore, the Concept Attainment learning model is effective as an alternative instructional strategy in elementary science education to enhance students’ conceptual understanding.